New development: E-government, eco-innovation, and public policies—shaping transparency, accountability, and corruption control in the EU - Kamal Si Mohammed (23073835) (2025)
Impact This article illustrates how e-government, eco-innovation, and public policies impact transparency, accountability, and the control of corruption within the EU. E-government has a consistent impact on governance, while eco-innovation has strong but time-bound effects; public policies enhance accountability when they are relatively recent. The study's implications are significant for public sector accountants, auditors, policy-makers and developers who both influence, and are influenced by, digital transformation in the public sector. Abstract This article examines how e-government, eco-innovation, and public policies shape transparency, accountability, and corruption control in the European Union from 2010 to 2022. Using a panel time-varying approach, the research indicates that e-government has the strongest and most durable impact on government quality, while the effects of eco-innovation and public policies are shorter lived. This study contributes to the literature by integrating digital governance, environmental innovation, and public policies into a unified model, offering new insights into how technological and environmental reforms jointly enhance accountability and transportability across EU institutions. Other Information Published in: Public Money & Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/09540962.2025.2597949